Neto and Giadán: The Last Two Spanish in the Qing Dynasty - Ramírez Ruiz, Raúl (Sinología hispánica. China Studies Review, 2017)
The present article examines the claim that Manuel Giadán Ruiz and Jose Antonio Neto González, Copper foundry workers, former employees of Rio Tinto Company Limited in Huelva, against the Government of the Republic of China in 1912 for breach of contract of the Imperial Copper Works. This enterprise was owned by the Gansu Provincial Government. Through this claim we can observe the causes of the failure of the modernization attempts carried out by the “Westernization Movement” in late Qing times; and also we can see the causes of frustration of Xinhai Revolution and the beginnings of the Republic of China. In particular, the “Neto and Giadan Claim” shows how the nascent Republic of China is unable to shake off the exploitation to which China was subject by the colonial powers. In fact, through this case, we see how the Republic of China was forced to yield to the economic claims of any European country, even to Spain, which at that time lacked the coercive or military capacity to impose its wishes on China. For the writing of this article, we have used original documentation from The Archive of Administration, The Archive of National History; The Archive of Historical Miner of Red River Fundation; The Archive of Huelva Province; Archivo of Huelva Diocesan, and The Archive Nerva Municipal. We have supplemented this documentation with the Belgian Foreign Ministry Archive and the personal archives of Belgian “technicians” led by "Belgian Mandarin" Paul Splingaerd and his son Alphonse. They were the managers of the industrialization process of Gansu Province launched by the Taotai of Lanzhou Peng Yingjia.